2021
DOI: 10.5206/mase/13886
|View full text |Cite
|
Sign up to set email alerts
|

Modeling SARS-CoV-2 spread with dynamic isolation

Abstract: Background: The SARS-CoV-2 pandemic is spreading with a greater intensity across the globe. The synchrony of public health interventions and epidemic waves signify the importance of evaluation of the underline interventions. Method: We developed a mathematical model to present the transmission dynamics of SARS-CoV-2 and to analyze the impact of key nonpharmaceutical interventions such as isolation and screening program on the disease outcomes to the people of New Jersey, USA. We introduced a dynamic isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Mathematical models can help understanding the disease dynamics better [14]. Several models exist which described the critical factors about infectious diseases with preventive measures [15,16,17,18,19,20,21,22]. However, modeling blood disorder disease like anemia may seem to be a bit different (as anemia is not infectious type) compared to that of infectious diseases but the insights from mathematical point of view is same.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models can help understanding the disease dynamics better [14]. Several models exist which described the critical factors about infectious diseases with preventive measures [15,16,17,18,19,20,21,22]. However, modeling blood disorder disease like anemia may seem to be a bit different (as anemia is not infectious type) compared to that of infectious diseases but the insights from mathematical point of view is same.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Laplace Adomian decomposition is an alternative way to derive an approximate explanation for the global infectious diseases like COVID-19 [7]. A model evaluated the impact of dynamic isolation and screening program on the epidemic of COVID-19 spread [8]. A modeling study found that with complete lockdown, the spread of COVID-19 will disappear, otherwise the disease will persist [9].…”
Section: Introductionmentioning
confidence: 99%